2004
DOI: 10.1302/0301-620x.86b4.14097
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting rates of infection and nonunion in intramedullary nailing

Abstract: We report a retrospective study over five years to determine the incidence of infection and nonunion after intramedullary nailing in fractures of 214 long bones; 122 femoral, 75 tibial and 17 humeral. The indications for nailing were trauma (n = 161), pathological fracture (n = 30) and nonunion (n = 23). There were 30 open fractures. The overall rates of deep infection and nonunion were 3.8% and 14.2%, respectively. Using multiple logistic regression analysis, we determined the relationships between deep infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(62 citation statements)
references
References 21 publications
4
53
1
4
Order By: Relevance
“…As noted by previous authors, it is difficult to treat and has a high financial impact [22,23]. With respect to femoral shaft fractures, IMN is an effective treatment option with nonunion rates less than 10%, regardless of the starting point [1,3], and infection rates in large series ranging from 1% to 3.8% [24]. The advantages of intramedullary fixation include early stable fixation, early mobilization of hip and knee joints, and less soft tissue damage.…”
Section: Discussionmentioning
confidence: 93%
“…As noted by previous authors, it is difficult to treat and has a high financial impact [22,23]. With respect to femoral shaft fractures, IMN is an effective treatment option with nonunion rates less than 10%, regardless of the starting point [1,3], and infection rates in large series ranging from 1% to 3.8% [24]. The advantages of intramedullary fixation include early stable fixation, early mobilization of hip and knee joints, and less soft tissue damage.…”
Section: Discussionmentioning
confidence: 93%
“…Rates of SSI after surgery for closed fractures range from 1 to 4% [2, 3]. Perioperative antibiotic prophylaxis can help prevent SSI, and studies have shown the benefit of administering antibiotics immediately before skin incision in closed fracture surgery [411].…”
Section: Introductionmentioning
confidence: 99%
“…Otro tipo es el clavo de Ender, ligeramente curvo, que también es biselado en su extremo distal (4,5,27) . Las complicaciones descritas en los clavos intramedulares incluyen separación de los fragmentos, cambios en la longitud del hueso, penetración articular, inmovilización inadecuada, fallas en el sistema de fijación (1,5,(28)(29) (Figura 20).…”
Section: A 16aunclassified